G153(P) Is tahini a superior alternative to commercial sesame allergen in skin prick testing?. (May 2019) - Sapsed, E; Vaughan, S; Wells, R; Fenton, S; Thomas, L; Christopher, A
Abstract : Aims: The allergy team at a secondary referral centre were concerned about small skin prick test (SPT) wheal size in known sesame allergic children. Other authors have reported more reliable results with SPT to tahini (Della-Torre et al. 2013). Therefore, we wanted to compare the results of SPT to sesame extract and tahini. Methods: All children where sesame SPT was indicated were included. Standard controls were used, and both commercial sesame and tahini were administered. Participants were also asked about their history of sesame exposure and eczema. Results: 19/50 children had a positive response (≥3 mm) to sesame and/or tahini. 10 had positive reactions to sesame and tahini, 9 were only tahini positive. 13 individuals had clinical history of sesame allergy. Ten tested positive for sesame and/or tahini. 5 of the 10 individuals tested positive only for tahini SPT, not for sesame. 5 tested positive for sesame and/or tahini that have a history of eating sesame without reaction, 3 positive only for tahini, 2 for both. Sesame had a mean reaction of 1.04 mm(s=1.84), tahini averaged 1.88 mm(s=2.42). A paired t-test supported an alternative hypothesis that tahini produces greater reaction than sesame (t=3.46, p=0.0006). There was no comparative difference seen in response to tahini in those children with eczema (n=26, t=0.296, p>0.05). There is statistically significant difference between exposure groups (eat sesame, never tried/empirical avoidance and previous reaction) in the difference between their tahini vs sesame wheal, (ANOVA (F(2, 44)= 6.744, p=0.03)). The difference in reaction size between tahini and sesame was larger in those that have previously reacted (mean=2.00±2.45)) compared to those that never tried/empirically avoided sesame (mean=0.11±0.85)(p=0.02). Conclusions: The results show greater reaction to tahini vs sesame, in the number of positive responses, and average size of response wheal. Importantly, the wheal size appears to be greater in those who have previously reacted compared to those who have avoided sesame. Those with eczema did not produce a greater mean difference between tahini and sesame wheal size, suggesting tahini is not acting as an irritant. Specific IgE and/or challenge testing could validate whether the additional positives (9/50) reflect true sesame allergy.